Dynamic Analysis of Stochastic Spruce Budworm Differential Model with Time Delay (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we consider a stochastic spruce budworm differentialmodel with time delay. Based on the nonnegative initial conditions, the existence and uniqueness of the global positive solution are easily found. Then, weobtain the ultimate boundedness of solution in mean under the same conditions. Furthermore, we verify that the sample Lyapunov exponent of solutionis less than a positive constant. Finally, numerical examples are presented toshow the consistency of the theoretical results.